2015
DOI: 10.1103/physrevd.91.045002
|View full text |Cite
|
Sign up to set email alerts
|

Efficient electroweak baryogenesis by black holes

Abstract: A novel cosmological scenario, capable to generate the observed baryon number at the electroweak scale for very small CP violating angles, is presented. The proposed mechanism can be applied in conventional FRW cosmology, but becomes extremely efficient due to accretion in the context of early cosmic expansion with high energy modifications. Assuming that our universe is a Randall-Sundrum brane, baryon asymmetry can easily be produced by Hawking radiation of very small primordial black holes. The Hawking radia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
(93 reference statements)
0
18
0
Order By: Relevance
“…In the cosmological context, baryogenesis is an important issue, and the current study motivates us to approach baryogenesis with the present extension, as also suggested in Ref. [18].…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…In the cosmological context, baryogenesis is an important issue, and the current study motivates us to approach baryogenesis with the present extension, as also suggested in Ref. [18].…”
mentioning
confidence: 74%
“…The energy density(18), depicted for α = 0 (solid line), α = 0.2 (dashed line) and α = 0.4 (dot-dashed line).…”
mentioning
confidence: 99%
“…Thus, at that length one should join the presented solutions with the quantum corrected one that includes both fields Λ and G, which consequently for even larger length scales should turn into the the classical Schwarzschild black hole. The present work could also be useful in other directions that utilize quantum corrected black holes to explain baryogenesis [63], stability issues [64], or dark energy [65].…”
Section: Discussionmentioning
confidence: 99%
“…Two Higgs doublet models(2HDM) are simple extensions of the SM in which the scalar sector of the SM is enlarged to contain new scalars [57][58][59][60][61][62]. Based on the couplings of the new scalars to quarks and leptons we can classify these models to several types such as type I, II or III [63].…”
Section: Cp Asymmetry Ofmentioning
confidence: 99%